The Inhibitory Activity of Compounds from Sophora japonica L. on Amyloid Beta Formation in Alzheimer’s Disease - Quang Huy, Nguyen; Hai Anh, Do Thi (VNU Journal of Science: Natural Sciences and Technology, 2020)
Two compounds (C2 and C6) were isolated and purified from Sophora japonica L. extract. Using nuclear magnetic resonance (NMR) spectroscopy, mass spectroscopy and thin layer chromatography, C2 and C6 were identified as quercetin and neohesperidin. The antioxidant activity of C2 and C6 (at concentration of 200 µM) is equivalent to vitamin C (at concentration of 0.57-1.14 µM/ml). Both compounds C2 and C6 have inhibitory activity on β-amyloid aggregation. At concentration of 1 mM of each compound, aggregation rate of β-amyloid (Amyloid form deposited in Alzheime's brain) are 51.14 and 80.57%, respectively, compar to control sample (89.64%).